Perceived social cohesion and depressive symptoms among internal migrants in China: The mediating role of social adaptation - Qu, Xiaomin; Qi, Xiang; Wu, Bei; Yu, Jiaojiao; Zhang, Haidong (Frontiers in Public Health, 2023)
Background Internal migrants are exposed to higher risks of depressive symptoms due to migration-related stress. It has been recognized that perceived neighbourhood social cohesion has direct and indirect associations with depressive symptoms. However, the pathway from perceived social cohesion to internal migrants’ depressive symptoms was less discussed. Objectives To assess mental health disparities among internal migrants. To investigate the association between social cohesion and depressive symptoms among urban-to-urban and rural-to-urban migrants and to examine the mediating role of social adaptation. Methods Data from the “2017 Urbanization and New Migrant Survey” was used, including 2,584 internal migrants age 18-65 from 10 cities in China. Social cohesion was measured by a six-item modified Community-level Cohesion Scale. Depressive symptoms was measured using the Center for Epidemiological Studies Depression Scale, and social adaptation was assessed by a single-item question of migrants’ adaptation to local life. Multivariate linear regression models were used to examine the association between social cohesion and depressive symptoms. Baron and Kenny’s mediation tests were conducted to examine the mediating role of social adaptation on the association. All analyses were adjusted using sampling weights to account for this survey’s sampling design. Results Rural-to-urban migrants were found to have more clinically significant depressive symptoms, lower perceived social cohesion, and fair or low social adaptation than urban-to-urban migrants (all p < 0.001). Being rural-to-urban migrants as compared with urban-to-urban migrants (Odds Ratio [OR] = 1.46, p < 0.001), had lower perceived social cohesion (OR = 1.46, p < 0.001), and poorer social adaptation (OR = 1.94, p < 0.001), are associated with higher odds of having clinically significant depressive symptoms. Social adaptation partially mediated the association between social cohesion and depressive symptoms by explaining 15.39% of its effect for urban-to-urban migrants and 18.97% for rural-to-urban migrants. Conclusions Findings from this study reveal mental health inequalities among internal migrants and demonstrate the importance of social adaption on the association between social cohesion and depressive symptoms. Social strategies and public policies are needed to build a more cohesive community that serves both local residents and internal migrants, especially rural-to-urban migrants.